Transport Management Practices and Safety Performance of Public Transport Organizations in Nairobi (British Journal of Multidisciplinary and Advanced Studies, 2025)
Road accidents cost the country, as is the case in other developing jurisdictions across the world, a loss of over 4% of the GDP. In Kenya, road accidents have been on the rise unlike in some developed nations. A substantial percentage of the road accidents involve public service vehicles. The transport management practices that could influence road safety performance of public sector organizations is yet to be empirically examined. This study sought to examine the effect of e-transport, fleet maintenance, fleet monitoring, and fleet technical capacity in Kenya. The study collect data from the 64 public transport organizations in County of Nairobi. Data was analyzed by applying descriptive and inferential statistics; which was be used to test the hypothesis of the study. This study established that transport management practices have a significant and substantial effect on the safety performance of public transport organizations. The study however established that public transport organizations in the county of Nairobi have a significantly low level adoption of e-transport, fleet maintenance mechanisms, and very low crew qualification requirements. The study recommends that adoption to a higher level, of these practices, could significantly reduce the number of accidents involving public sector transport organizations in Kenya.